Factors associated with nursing students’ support for the implementation of environmental measures in healthcare services to reduce carbon footprint: a multisite cross-sectional correlation study - Jiayi Xu; Yibo Wu; Yifan Wu; Juanxia Miao; Jiukai Zhao; Kunshuo Du; Yu Yang; Shuang Zang (BMC Nursing)
Abstract Background Reducing the carbon footprint in healthcare services is essential for combating climate change and promoting sustainable health systems. Nursing students play a key role in supporting environmentally friendly practices. This study aimed to assess the level of support among Chinese nursing students and to explore the factors associated with their support. Methods A cross-sectional correlation study was conducted using data from 1871 nursing students who participated in the 2024 Chinese Population Psychology and Behavior Survey (PBICR). Data were collected between June 23 and September 29, 2024, through a nationally representative stratified and quota sampling approach. Based on the social ecological model, this study examined a comprehensive set of factors potentially associated with nursing students’ support for the implementation of environmental measures in healthcare services to reduce carbon footprint, including intrapersonal-level variables (e.g., personality traits, self-efficacy, health literacy, etc.), interpersonal-level variables (e.g., perceived social support and family health), institutional-level variables (e.g., academic stage), community-level variables (e.g., place of residence, hukou status, per capita family monthly income), and policy-level variables (e.g., medical insurance). Univariate generalized linear modeling and multivariable stepwise regression were employed to identify significant factors of support for environmental measures in healthcare services. Results The average score for supporting the implementation of environmental measures in healthcare services to reduce carbon footprint was 70.93 ± 23.51, indicating an above-moderate level of support among 1871 Chinese nursing students. Significant predictors of nursing students’ support level included gender (β = 0.09), extraversion (β = − 0.17), agreeableness (β = 0.11), internal health belief (β = 0.10), meaning in life (β = 0.07), quality of life (β = 0.14), digital health use (β = − 0.09), familiarity with the Sustainable Development Goals (β = 0.31), family health (β = 0.08), and academic stage (β = 0.11) (all P ≤ 0.002). Notably, familiarity with the Sustainable Development Goals emerged as the strongest positive predictor. The model explained 23.3% of the variance (adjusted R² = 0.233, F = 57.66, P < 0.001). Conclusions Support level among Chinese nursing students was above moderate but needs improvement. The findings provide a basis for developing targeted educational strategies to enhance environmental engagement in nursing. Clinical trail number Not applicable.